2003
DOI: 10.3354/dao057001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of novel Helicobacter spp. from the gastric mucosa of harp seals Phoca groenlandica

Abstract: Since the recent discovery of Helicobacter cetorum in cetaceans and its role in the development of gastritis, speculation has existed as to whether pinnipeds have Helicobacter spp. associated gastritis and peptic ulcer disease. The gastric mucosa of 4 stranded harp seals Phoca groenlandica from the Massachusetts coastline were assessed for Helicobacter spp. by culture and PCR. We cultured 2 novel Helicobacter spp. from the pyloric antrum of 1 of the 4 harp seals studied, and identified these by PCR in 2 of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…In a previous study, we demonstrated that strains with flexispira morphology fell into at least 10 Helicobacter taxa by 16S rRNA gene sequence comparison (14). Since that paper was published, Helicobacter aurati and strain MIT 01-5529A, isolated from a seal, representing two additional flexispira taxa, have been described (24,44). As noted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, we demonstrated that strains with flexispira morphology fell into at least 10 Helicobacter taxa by 16S rRNA gene sequence comparison (14). Since that paper was published, Helicobacter aurati and strain MIT 01-5529A, isolated from a seal, representing two additional flexispira taxa, have been described (24,44). As noted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The S-shaped BTP isolates showed 96% similarity to Helicobacter sp. MIT 01-6242, isolated from the gastric mucosa of harp seals (Phoca groenlandica) (13). The comparison of the 16S rRNA gene sequences obtained in this study to other sequences from GenBank confirmed that the 18 isolates potentially were novel Helicobacter species.…”
Section: Resultsmentioning
confidence: 74%
“…While any of these species may have been responsible for the development of gastritis in this animal, they also may have been mere bystanders (3), as species of Helicobacter, like those of Wolinella, may be nonpathogenic in their natural host (25,26). Indeed, with the detection of Helicobacter species in the gut of a clinically healthy sea lion (Portia) exhibiting no significant pathological features consistent with Helicobacter infections in other animals (16,17), the role of Helicobacter in this host requires further examination.…”
Section: Discussionmentioning
confidence: 99%
“…While no spiral-shaped organisms were observed in this (or the control) specimen, such Helicobacter-like organisms may not always be detected by standard staining procedures such as HE staining (4). Despite this limitation, its detection in the gut of this host, given the ability of other species to cause similar conditions of disease in other marine mammals (16,17), is novel and reflects the potential for multiple genera of the family Helicobacteraceae to infect this host. Coinfection of a host by closely related taxa has some precedence in the literature and has been reported for Campylobacter, Helicobacter, and Wolinella species (3,24).…”
Section: Discussionmentioning
confidence: 99%